To solve the equation \( \frac{1}{3}(6x - 9) = -33 \), you can follow these steps in order:
-
Eliminate the fraction: Multiply both sides of the equation by 3 to get rid of the fraction. \[ 3 \cdot \frac{1}{3}(6x - 9) = 3 \cdot (-33) \] Which simplifies to: \[ 6x - 9 = -99 \]
-
Isolate the term with \(x\): Add 9 to both sides of the equation. \[ 6x - 9 + 9 = -99 + 9 \] Simplifying gives: \[ 6x = -90 \]
-
Solve for \(x\): Divide both sides by 6. \[ x = \frac{-90}{6} \] Which simplifies to: \[ x = -15 \]
Thus, the correct order of the steps to solve the equation is:
- Multiply by 3.
- Add 9.
- Divide by 6.
So the final solution is \( x = -15 \).